2019
DOI: 10.1038/s41386-019-0390-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulation of mu opioid and nociceptin/orphanin FQ peptide (NOP) receptors on alcohol drinking in rhesus monkeys

Abstract: Alcohol use disorder (AUD) persists as a devastating public health problem; widely effective pharmacological treatments are needed. Evidence from rodent models suggests that stimulating brain receptors for the neuropeptide nociceptin/orphanin FQ (NOP) can decrease ethanol drinking. We characterized the effects of the mu opioid peptide (MOP) receptor agonist buprenorphine and the buprenorphine analog (2S)-2-[(5R,6R,7R,14S)-N-cyclopropylmethyl-4,5-epoxy-6,14-ethano-3-hydroxy-6 methoxymorphinan-7-yl]-3,3-dimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 83 publications
(144 reference statements)
0
11
0
Order By: Relevance
“…Importantly, high SUV values in selective brain areas including putamen, globus pallidus, cortex, and hippocampus warrants additional studies to investigate microtubule regulation in models of diseases such as AUD and AD. Further studies will include [ 11 C]MPC-6827 PET imaging in NHP models of substance abuse disorder, including alcohol and cocaine self-administration [39,40], and NHP model of AD [38]. We will also characterize the metabolite analyses, arterial input functions, and specificity studies, and correlate the data with PET images using sophisticated pharmacokinetic modeling [31].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, high SUV values in selective brain areas including putamen, globus pallidus, cortex, and hippocampus warrants additional studies to investigate microtubule regulation in models of diseases such as AUD and AD. Further studies will include [ 11 C]MPC-6827 PET imaging in NHP models of substance abuse disorder, including alcohol and cocaine self-administration [39,40], and NHP model of AD [38]. We will also characterize the metabolite analyses, arterial input functions, and specificity studies, and correlate the data with PET images using sophisticated pharmacokinetic modeling [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike classical full μ receptor agonists, such as heroin, and fentanyl or partial agonists, such as buprenorphine, BU08028 is not self-administered by rhesus monkeys (Ding et al, 2016). A more recent study also showed that buprenorphine and BU08028 both acutely and chronically decrease alcohol drinking in rhesus monkeys, with BU08028 showing higher potency than buprenorphine (Flynn et al, 2019). Together, these findings suggest that BU08028 can mimic the therapeutic effects of buprenorphine while carrying lower risk for abuse liability.…”
Section: Introductionmentioning
confidence: 98%
“…This is the first evidence demonstrating the identification of a novel bifunctional NOP/MOP agonist that inhibits abuse liability of prescription opioid oxycodone with behavioral selectivity. Moreover, a recent report demonstrated that BU08028 selectively attenuate alcohol intake without affecting food-maintained operant behaviors in NHPs (Flynn et al, 2019). Acute systemic administration of BU08028 decreased ethanol drinking, and the effective doses of BU08028 were lower than that of buprenorphine.…”
Section: Tre Atment Of Drug Abus E By Coac Tivati On Of Nop and Mop Recep To R Smentioning
confidence: 96%
“…Acute systemic administration of BU08028 decreased ethanol drinking, and the effective doses of BU08028 were lower than that of buprenorphine. In addition, chronic dosing of BU08028 also attenuated ethanol drinking, with the effects maintained for several weeks without inducing tolerance and adverse effects (Flynn et al, 2019). Given that AT-121 and BU08028 alone did not produce reinforcing effects (i.e., abuse liability) in NHPs, bifunctional NOP/MOP partial agonists may have great therapeutic potential for treating not only pain but also substance use disorders with fewer side effects.…”
Section: Tre Atment Of Drug Abus E By Coac Tivati On Of Nop and Mop Recep To R Smentioning
confidence: 97%